2016
DOI: 10.1242/jcs.174631
|View full text |Cite
|
Sign up to set email alerts
|

Activated microglia cause reversible apoptosis of pheochromocytoma cells, inducing their cell death by phagocytosis

Abstract: Some apoptotic processes, such as phosphatidylserine exposure, are potentially reversible and do not necessarily lead to cell death. However, phosphatidylserine exposure can induce phagocytosis of a cell, resulting in cell death by phagocytosis: phagoptosis. Phagoptosis of neurons by microglia might contribute to neuropathology, whereas phagoptosis of tumour cells by macrophages might limit cancer. Here, we examined the mechanisms by which BV-2 microglia killed co-cultured pheochromocytoma (PC12) cells that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…Recently it has been shown that activated microglia produce nitric oxide, which promotes transient caspase activity and phosphatidylserine exposure in neurons, prior to phagocytosis. 18 However, it is not clear how widely this mechanism is used, or whether other mechanisms are used by phagocytes to promote the death of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that activated microglia produce nitric oxide, which promotes transient caspase activity and phosphatidylserine exposure in neurons, prior to phagocytosis. 18 However, it is not clear how widely this mechanism is used, or whether other mechanisms are used by phagocytes to promote the death of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Reversal of apoptosis is an unusual process, which is relatively less known than canonical apoptosis. As has been shown in brain cells, activated microglia could rescue apoptotic cells through reversible exposure of PS on the cell surface (43). Furthermore, it was shown that in the early stages of p-53induced apoptosis, removal of the apoptotic stimuli could reverse the apoptotic progress (44).…”
Section: Discussionmentioning
confidence: 75%
“…Beyond parthanatos and mitochondrial permeability transition, other mechanisms involved in neuronal death include intrinsic and extrinsic pathways of the apoptotic process, autophagy, phagoptosis (phagocytosis), oncosis, necroptosis, ferroptosis, sarmoptosis, autosis, autolysis, paraptosis, and pyroptosis . NO has been implicated in all these mechanisms . Figure charts the pathways associated with NO concentration fluctuations.…”
Section: No's Double‐edged Sword: a Cause Of Ocular Pathologymentioning
confidence: 99%